Higgs compositeness in Sp(2N) gauge theories – Determining the low-energy constants with lattice calculations - Biagio Lucini (EPJ Web of Conferences, 2018)
As a first step towards a quantitative understanding of the SU(4)/Sp(4) compositeHiggs model through lattice calculations, we discuss the low energy eective fieldtheory resulting from the SU(4) ! Sp(4) global symmetry breaking pattern. We thenconsider an Sp(4) gauge theory with two Dirac fermion flavours in the fundamental representationon a lattice, which provides a concrete example of the microscopic realisationof the SU(4)/Sp(4) composite Higgs model. For this system, we outline a programmeof numerical simulations aiming at the determination of the low-energy constants of theeective field theory and we test the method on the quenched theory. We also report earlyresults from dynamical simulations, focussing on the phase structure of the lattice theoryand a calculation of the lowest-lying meson spectrum at coarse lattice spacing.